2017
DOI: 10.1016/j.pan.2017.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of early nutrition: the benefits of enteral feeding compared to a nil per os diet not only in severe, but also in mild and moderate acute pancreatitis

Abstract: Abstract:The recently published guidelines for acute pancreatitis (AP) suggest that enteral nutrition (EN) should be the primary therapy in patients suffering from severe acute pancreatitis (SAP); however, none of the guidelines have recommendations on mild and moderate AP (MAP). A meta-analysis was performed using the preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P). The following PICO (problem, intervention, comparison, outcome) was applied: P: nutrition in AP; I: entera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“…Based on these findings, 8 TAs with the best‐quality evidence were selected for further analysis, as prioritized by points on rubric scores (Table ). They included cross‐disease malnutrition, sepsis, surgical complications, HACs, congestive heart failure, COPD, GI cancer, and pancreatitis …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, 8 TAs with the best‐quality evidence were selected for further analysis, as prioritized by points on rubric scores (Table ). They included cross‐disease malnutrition, sepsis, surgical complications, HACs, congestive heart failure, COPD, GI cancer, and pancreatitis …”
Section: Resultsmentioning
confidence: 99%
“…They included cross-disease malnutrition, 7,24-33 sepsis, 27,34-41 surgical complications, [42][43][44][45][46][47][48][49][50] HACs, [51][52][53][54][55][56][57][58] congestive heart failure, 9,[59][60][61][62][63][64][65][66][67][68] COPD, 8,9,16,[69][70][71][72][73] GI cancer, [74][75][76][77][78][79][80][81][82] and pancreatitis. [83][84][85][86][87][88]…”
Section: Task 1 Literature Analysismentioning
confidence: 99%
“…En un metaanálisis de Márta y cols se analizaron estudios clínicos randomizados acerca de NET en PAL y moderadas, dicho estudio concluyó que si bien no existen diferencias en la morbimortalidad entre pacientes que reciben NET y los que reciben tratamiento estándar de NXB, algunos parámetros secundarios como la estadía hospitalaria serían ventajas en los grupos con NET. Por los resultados obtenidos y la bibliografía consultada, podemos sostener que la NET es segura y puede formar parte del tratamiento de las PAL (36) . También según el presente trabajo debemos rechazar nuestra hipótesis, ya que la NET aumentó la respuesta inflamatoria medida por PCR y disminuyó los valores de albuminemia en el G1.…”
Section: Discussionunclassified
“… 34 Importantly, EN decreases mortality but also reduces the frequency of multiorgan failure and the need for interventions in patients with SAP. 35 No data are available on whether early or on-demand nutrition/energy supply is beneficial in SAP. The recently published Dutch PYTHON study suggests that there is no difference between early and on-demand enteral tube feeding in SAP, but patients may have received an insufficient amount of energy at the early phase of the disease.…”
Section: Introductionmentioning
confidence: 99%
“… 42 In order to obtain stronger evidence of the usefulness of early EN in MAP and SAP, we performed a systematic review and meta-analysis which showed that early EN can be beneficial in both MAP and SAP. 35 However, we also realised the lack of multicentre randomised control trials addressing energy intake in the early phase of AP.…”
Section: Introductionmentioning
confidence: 99%